Issues With the Use of Solar Dryers - Ramazonova Fotima Yorboyevnа (Zien Journals, 2022)
This article discusses the issues of identifying and classifying the most efficient options for a solar dryer, the study and analysis of different types of solar dryer appearances and performance processes.
Keywords: dryer; heater; research results; hot water